2013
DOI: 10.1179/1465313313y.0000000072
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial investigating pain associated with superelastic nickel–titanium and multistranded stainless steel archwires during the initial leveling and aligning phase of orthodontic treatment

Abstract: Objective:To investigate and compare the effects of superelastic nickel–titanium and multistranded stainless steel archwires on pain during the initial phase of orthodontic treatment.Design:A double-blind two-arm parallel design stratified randomized clinical trial.Setting:A single centre in India between December 2010 and June 2012. A total of 96 participants (48 male and 48 females; 14.1±2.1 years old) were randomized (stratified on age, sex and initial crowding) to superelastic nickel–titanium or multistran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 24 publications
(55 reference statements)
4
42
1
Order By: Relevance
“…1,2,5,6 However, this claim made by authors of previous studies has an inherent flaw, as rightly pointed out by the authors of a recent study. 7 Since none of the previous studies reported the actual time of force application and the subsequent time of pain assessment, therefore, it is difficult to ascertain the actual time of peak intensity level. After controlling for this factor of variation i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,5,6 However, this claim made by authors of previous studies has an inherent flaw, as rightly pointed out by the authors of a recent study. 7 Since none of the previous studies reported the actual time of force application and the subsequent time of pain assessment, therefore, it is difficult to ascertain the actual time of peak intensity level. After controlling for this factor of variation i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that most orthodontic patients report that pain commences during the first couple of hours of orthodontic force application, reaches peak intensity level after one day, and then eventually declines to normal levels after 7 days. [4][5][6][7] Bergius et al 5,6 report that the experience of pain varied substantially among subjects after elastic separators placement, suggesting BS variation in orthodontic pain perception. The authors further report that patient gender had a significant influence on orthodontic pain perception.…”
Section: Introductionmentioning
confidence: 99%
“…16 A similar finding was reported in another study; however, superelastic wires had a significantly higher pain at peak level. 18 When comparing conventional Nitinol wires to superelastic Sentalloy wires over 1 week following archwire placement, a significant difference in the overall pain response could not be found. 17 However, Fernandes et al 17 found that conventional Nitinol wires induced significantly higher pain levels than superelastic Sentalloy wires at 4 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies evaluated the pain intensity experienced by patients during the initial alignment stage of treatment with different archwires. [16][17][18] Bearing these studies in mind, there are no definite conclusions as to which archwire is associated with the least pain. 19 Therefore, the aim of this study was to evaluate the pain experience during the initial aligning phase of orthodontic treatment with three types of NiTi wires: superelastic NiTi, thermoelastic NiTi, and Nitinol aligning archwires.…”
Section: Introductionmentioning
confidence: 99%
“…Among various age groups, children report pain lesser as compared to adults. In the same age group, females report greater pain experiences as compared to the males 7,8 . It is dependent upon various factors including sex, age, pain threshold, magnitude of force, and emotional status.The forces which are applied on teeth trigger an inflammatory response which involve factors which form the basis of tooth movement i.e.…”
Section: Introductionmentioning
confidence: 84%